Communication and networking International Conference, FGCN 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings, Part II - Kim, Tai-hoon; Adeli, Hojjat; Fang, Wai-chi; Vasilakos, Thanos; Stoica, Adrian; Patrikakis, Charalampos Z.; Zhao, Gansen; Villalba, Javier García; Xiao, Yang (Springer Berlin Heidelberg, 2011)
The two volume set, CCIS 265 and CCIS 266, constitutes the refereed proceedings of the International Conference, FGCN 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of future generation communication and networking.